The Role Of Land Deed Official (PPAT) In Application Of Transfer Function On Agricultural Land To Be Non- Agricultural In Tegal (Certificate Study Of Ownership Right Number 998 / Pakembaran) - Mochammad Yefrie Dwi Oga; Lathifah Hanim (Jurnal Akta, 2019)
The purpose of this study was to determine: 1) The role of the Land Deed Official (PPAT) in registration of rights to land conversion of agricultural to non-agricultural to residential in Tegal. 2) The procedure of registration of land rights over the function of agricultural to non-agricultural to residential in Tegal. 3) Obstacles and solutions of conversion rights over agricultural land into non-agricultural to residential in Tegal. This study uses empirical juridical approach or socio-legal research. Data collected through literature, observation and interviews. Based on data analysis concluded that: 1) The role of PPAT in enrollment over the function of rights over agricultural land into non-agricultural to residential houses which provide information on the law relating to the procedure of land conversion and registration of land rights after deters conversion and the making of letters or deeds relating for their particular legal acts such as the breakdown of plot, behind the name, as well as buying and selling land. 2) The procedure of registration of land rights over the function of agricultural to non-agricultural to residential implemented through several stages of the formation of the assessment team, the assessment of land use change object, the trial of the determination, the recommendations and the issuance of a decision on approval of land use changes. 3) Obstacles and solutions in the conversion of agricultural land rights into non-agricultural to residential namely population growth, land agricultural diminishing and changing the status of land use. The solution in the conversion of rights over agricultural land into non-agricultural to residential houses of government is more emphasis on the rules on agricultural land and non-agricultural order later on agricultural land does not decrease faster than society itself should be aware of the importance of agricultural for food security community own.Keywords: Notary / PPAT; Role; Registration; Transfer Function; Land.